Deconstructing soil detachment: integrated assessment of soil properties, root characteristics, and hydraulics under diverse land uses on the Chinese loess plateau - JianFang Wang; JiaMing Li; GuoBin Liu; WeiWei Ma; Bing Wang (CATENA, 2026)

Impacts of carbon source type on metabolic pathways and microbial synergy in the simultaneous anammox and endogenous denitrification process - Wenlong Liu; Yuyan Zhang; Chenhao Yue; Jiaming Wang; Jun Li; Huijie Lu; Shilong He; Yongzhen Peng (Bioresource Technology, 2026)

LARIS: a local-state active reasoning and integrated switching framework for robotic harvesting under partial observability - Nianzu Dai; Jiaming Fang; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2026)

Origin of Early Cretaceous magmatism and its linkage with Cu–Fe–Au skarn mineralization in the Tonglushan ore field, eastern China: Evidence from whole-rock, zircon, and apatite geochemistry - Ming Zhang; Xiangzhou Li; Yanyan Zhao; Shichao Shang; Jiaming Zhou; Wan Huang; Yiheng Liu; Ziqing Yan; Xiaoyang Liu; Jun Tan (Lithos, 2026)

Constant-voltage triboelectric nanogenerator coupled with an intermittent speed-up mechanism and bionic jellyfish blades for low-speed water flow energy harvesting - Chenxi Li; Yongle Zhou; Fupu Xie; Jiaming Zhang; Yi Li; Hongwei Wang; Kaisheng Li; Zihao Li; Siyuan Liu; Tianyu Li (Chemical Engineering Journal, 2026)

Amplification-free electrochemiluminescence biosensors based on peptide-templated gold nanocluster and CRISPR-Cas12a for Mycobacterium tuberculosis IS6110 detection - Lingjun Cheng; Qingmei Yang; Yuanyuan Yang; Yufeng Wang; Qingfei He; Zhiyan Zou; Canping Su; Jiaming Chen; Yinhuan Liu; Guolin Hong (Analytica Chimica Acta, 2026)

Sustainable urban transitions in resource-based cities: How transition willingness translates into external green technology acquisition - Jiachuan Liu; Peiyuan Zhang; Jiaming Li; Shuo Lu; Wenzhong Zhang (Sustainable Production and Consumption, 2026)

De-localization of global cities: How advanced producer services exacerbate regional spatial inequality? - Jiaming Li; Jiachuan Liu (Land Use Policy, 2026)

LvBlimp1 and LvHes1 coregulate the function of macrophage-like phagocytes in shrimp hemolymph - Jiaming Liu; Yaohui Chen; Wenyong Jiang; Zhiyao Lu; Nuo Lin; Qingyun Liu; Xiuli Chen; Yongzhen Zhao; Fan Wang (Fish & Shellfish Immunology, 2026)

Study on the influence of different cold shock methods on the mechanical properties and rockburst proneness of high-temperature monzogranite - Jiaming Li; Xinyu Liu; Shuguang Zhang; Shibin Tang; Xiang Huang; Wenbo Liu (Engineering Geology, 2026)

A multifunctional photothermal nanoplatform integrating CD47 degradation and metabolic reprogramming for potentiated tumor immunotherapy - Jiaming Zhang; Chao Chen; Zhousheng Lin; Zeyu Liu; Juan Zhang; Jieying Qian; Xiaowan Huang; Yunjiao Zhang; Guangyu Yao (Chemical Engineering Journal, 2026)

Thermal-buffering cellulose aerogels with competitive hydrogen bonding: Dual-enthalpy synergy for efficient solar desalination - Mengqi Lu; Shuyue Zhang; Jiangquan Yang; Wei Li; Shuangfei Wang; Shouxin Liu; Jiaming Sun; Shuangxi Nie (Chemical Engineering Journal, 2026)

Thermally regenerable zwitterionic metal-organic frameworks with proton transfer properties for efficient lithium extraction - Xu Wu; Qian Guan; Mengyu Tang; Yue Zheng; Zhipeng Luo; Qiuyue Liu; Jiaming Gan; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Microbes Isolated from Ailanthus altissima Leaves Contribute to Samia cynthia’s Tolerance to the Toxic Quassinoid Diterpenoid - Jiaming Zhang; Juan Hua; Yangyang Wang; Jiayi Liu; Zhen Yang; Yanqun Liu; Shihong Luo (Journal of Chemical Ecology, 2026)

Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

Cyclic biomineralization by incorporating iron-oxidizing and sulfate-reducing microorganisms for sustainable iron removal and sulfur recovery from acid mine drainage: Efficiency and mechanism - Xingjie Wang; Ling Liu; Yuxuan Yang; Jiaming Du; Liyuan Ma; Jie Tang; Peng Liu; Jianwei Zhou (Minerals Engineering, 2026)

Machine vision-based impurity content assessment of paddy grains for pre-storage quality monitoring - Liu Yang; Xinfeng Hu; Can Shu; Jiaming Wang; Nianwu Wei; Tianqing Liu; Qian Liu; Menghao Zhao; Zhiwei Liu; Shaoyun Song (Journal of Stored Products Research, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Air plasma constructing multi-defects in NiFe metal-organic frameworks for enhanced electrocatalysis - Jiaming Zhao; Yilin Li; Xuchen Miao; Yuanbo Wang; Xingyun Li; Yubao Liu; Zhiliang Liu; Guoling Li (Chemical Engineering Journal, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Machine learning-assisted smartphone fluorescence sensing for ultrasensitive and point-of-care testing of acid phosphatase - Fusheng Zhong; Jiaming Zhang; Huaxi Ruan; Tonglong Yang; Jinbo Cao; Liangliang Peng; Jinhui Liu; Qingqing Deng; Li Wang (Analytica Chimica Acta, 2026)

High-accuracy estimation of global site-level soil heterotrophic respiration through Geo-XGBoost integration with expanded datasets and remote sensing - Jie Liu; Ni Huang; Luying Zhu; Jiaming Chang; Yuting Shi; Zheng Niu; Dewen Cai; Li Wang (Agricultural and Forest Meteorology, 2026)

Pixel relationship-constrained weakly supervised semantic segmentation for remote sensing images: enhancing CAM integrity and pseudo-label quality - Jiaming Fan; Dali Chen; Yang Liu; Shixin Liu (International Journal of Remote Sensing, 2026)

Exploring the carbon reduction effects of different rooftop utilization modes for public buildings - A regional perspective - Peng Wang; Yihao Yang; Jiawen Liu; Xiangyu Min; Lei Huang; Jiaming Wang (Sustainable Cities and Society, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

3D laser scanning-based geometry reconstruction and stress evaluation of a KK-type cast steel node for offshore wind turbine jacket structures - Feng Shi; Hui Jin; Lu Xu; Jiaming Liu; Jiahao Hu; Haihan Jiao (Ocean Engineering, 2026)

Garnet microtextures and geochemistry of the Tonglushan Cu–Fe–Au skarn deposit (Edong district): Constraints on fluid evolution and skarn mineralization - Ming Zhang; Xiangzhou Li; Ziqing Yan; Shichao Shang; Wan Huang; Yanyan Zhao; Jiaming Zhou; Xiaoyang Liu; Jingui Huang; Jun Tan (Journal of Geochemical Exploration, 2026)

Effects of microenvironmental factors on water-insoluble precipitation induced by soybean urease - Chongda Duan; Jiaming Zhang; Yi Luo; Yanzi Sun; Jiaxing Liu; Xiang Lv (Journal of Environmental Chemical Engineering, 2026)

Bioenrichment of conjugated linoleic acid in oil-in-water (O/W) emulsion by Niubie as a natural biocatalyst - Yusen Wu; Xiaobi Yang; Na Liu; You Chen; Jiaming Gu; Likang Qin; Song Miao (Food Bioscience, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Polyphase of uranium mineralization in granite-related deposits: Insights from the geochronology and geochemistry of pitchblende and coffinite in the Xiwang uranium deposit, South China - Bin Liu; Weifeng Chen; Haidong Li; Jiaming Qi; Liang Qiu; Hongfei Ling (Applied Geochemistry, 2026)

A bibliometric analysis of global duckweed research (2015–2025): research trends, international collaborations, and emerging themes - Jiaming Wang; Zhenghong Peng; Zuoyue Duan; Yaojun Zhou; Hongling Zhu; Shijun You; Zhiyi Peng; Mengni Shi; Qulian Guo; Wenjun Liu; Ling Guo (Hydrobiologia, 2026)

Synergistic architecture and dynamic adaptability in heterogeneous catalysts for CO2 hydrogenation - Jiao Liu; Xingyi Cen; Jiaming Lin; Junrong Yue; Duo Sun; Fang Wang (Journal of Environmental Sciences, 2026)

A novel approach to distinguish the respective contributions of galvanic effect and reactive oxygen species on sulfide mineral dissolution: Insights from stibnite and pyrite - Xiaoqian Li; Jingxuan Qiu; Xingjie Wang; Jiaming Du; Deng Liu; Chun Li; Hongmei Wang; Liyuan Ma (Chemical Geology, 2026)

High Cholesterol Facilitates Ovarian Androgen Production and Contributes to the Development of Polycystic Ovary Syndrome - Yue Liu; Shourui Hu; Xiaofan Liang; Jiaming Zhang; Yiming Qin; Chunxuan Geng; Yuqing Zhang (Phenomics, 2026)

Olfactory Valence-Processing Deficits and Aberrant Brain Network Connectivity Underlie Social Dysfunction in Shank3-/- ASD Model Mice - Dingding Yang; Qian Liu; Hangjun Ran; Teng Xue; Yifan Lu; Xiao Yang; Jiaming Wang; Ling Liu; Wenting Wang; Binbin Nie; Guohong Cai; Shengxi Wu (Neuroscience Bulletin, 2026)

Identifying the environmental drivers of the distribution of carbon isotopes in global inland waters - Jiahui Shi; Lixiao Ni; Jiaming Liu; Yushen Ma; Yiping Li; Carlo Gualtieri (Water Research, 2026)

Nitrogen uptake preference of Avicennia marina and Aegiceras corniculatum in simulated saline water under varying salinities - Dejian Su; Jiaming Hu; Chutong Zhang; Yushuang Yang; Xiuru Zhu; Jian Guan; Yong Liu (Marine Environmental Research, 2026)

Paeoniae Radix Rubra extract inhibits largemouth bass ranavirus (LMBV) replication by suppressing inflammatory response and oxidative stress - Yang Liu; Dasen Li; Wenyan Liu; Chutong Zhang; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

Spatial mismatch and inequality between ecological pressure and economic benefits embodied in agricultural trade - Kaige Lei; Jiaming Zhang; Yan Li; Xinhui Feng; Jiayu Yang; Li Hou; Jianguo Liu (Environmental Impact Assessment Review, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Tracking 3D desiccation crack evolution and permeability dynamics in expansive soil - Yun Peng; Jiaming Zhang; Yi Luo; Tianle Liu; Mingjian Hu; Shuai Liu (Bulletin of Engineering Geology and the Environment, 2026)

Petrogenesis of Yanshanian granites in the Guidong complex, Northern Guangdong: Implications for uranium mineralization - Haiyang Wang; Changqian Ma; Jiayong Pan; Fujun Zhong; Fei Xia; Xiangping Gu; Guanghua Liu; Zhengle Chen; Jungang Liu; Jiaming Qi (Acta Geochimica, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Corrigendum to “Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data” [Int. J. Coal Geol. 320 (2026) 104999] - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Engineering a Ga-Mn-Zr trimetallic oxide to modulate intermediates for highly selective light olefin synthesis from syngas - Xiuyun Jiang; Songpeng Cheng; Qingxiang Ma; Guangbo Liu; Jinhu Wu; Caixia Zhu; Reubroycharoen Prasert; Jiaming Liang; Xinghua Gao; Yingluo He; Guohui Yang; Noritatsu Tsubaki (Chemical Engineering Journal, 2026)

Aerodynamic and wake characteristic analysis of a dual-rotor wind turbine under surge motion based on modified actuator line model - Mengshang Zhao; Kai Wang; Siqi Chen; Jiaming Liu; Yuan Li (Ocean Engineering, 2026)

Investigation of CO2 absorption and desorption performance and mechanism of aqueous [TETAH][Im] in a PTFE hollow fiber membrane contactor - Chunyun Zhou; Yanbin Yun; Chang Li; Jia Liu; Jiaming Mao; Wenjuan Yang; Haiyan Huang; Guoqiang Zhuang; Meng Li (Journal of Environmental Chemical Engineering, 2026)

Identification of electromechanical participation matrices via scaled-derivative DMDc for improved PPF active vibration control of thin-walled structures - Qinshan Ouyang; Longlei Dong; Jian Liu; Jiaming Zhou (Engineering Structures, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

Circadian Rhythm Disorder-Related Dysfunctions are Exacerbated by Aging and Ameliorated by Time-Restricted Feeding - Fengjiao Huo; Qing Liu; Shuaishuai Zhang; Xiaorui Liu; Shuyao Lv; Meili Zhao; Yue Liu; Xiaoqi Zhu; Ce Huang; Shengyu Feng; Hao Wang; Siling Xu; et al. (Neuroscience Bulletin, 2026)

Impacts of anthropogenic activities on habitat fragmentation and their spatial heterogeneity in the Himalayas - Jiaming Li; Jiachuan Liu (Journal of Geographical Sciences, 2026)

Unintended environmental risks of regional PV expansion: A climate-adjusted lifecycle analysis for sustainable deployment - Jiawen Liu; Liangzhong Li; Yangyang Wu; Jiaming Wang; Futian Ren; Peng Wang; Lei Huang (Journal of Environmental Management, 2026)

The E3 ligase RNF5 facilitates viral replication by suppressing innate immune responses in grouper - Yanqi Zhao; Xiaohui Zheng; Siting Wu; Minyao Bi; Jiaming Hu; Shaojie Liu; Jingguang Wei; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Research on bearing capacity of laser welding reinforcement of spherical joint region of spatial grid structure - Caibao Liu; Xiongyan Li; Wei Wang; Suduo Xue; Jiaming Yang (Engineering Structures, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Hybrid framework combining machine learning with mechanism models for enhanced forecasting of biomass gasification products - Jiaming Song; Zongqi Chen; Haining Tang; Hong Ding; Shiliang Wu; Zhou Liu; Feng Gong (Bioresource Technology, 2026)

Urban Pluvial Flood Maximum Water Depth Prediction Using a Transformer-CNN Hybrid Deep Learning Model with Data Augmentation - Ziqi Liu; Dejun Zhu; Jiaming Luo; Danxun Li (Water Resources Management, 2026)

Non-uniform salinity combined with localized nitrogen supply improves water use efficiency and fruit visual and storage qualities in tomato - Jinjing Liu; Zhenchang Wang; Yongfeng Huang; Yuexiong Wang; Weixing Wen; Kexin Chen; Yanmin Bi; Yating He; Jiaming You; Yaosheng Wang (Plant and Soil, 2026)

Different geographical patterns and assembly mechanisms of phytoplankton and benthic diatoms: a case study in a cold temperate wetland cluster - Yongxu Duan; Zhengxun Li; Jiaming Liu; Zheng Hou; Henglin Xiao; Yan Liu; Yawen Fan; Xinxin Lu (Hydrobiologia, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Experimental investigation of phase lag in compound channels under repeated unsteady flow cycles - Jiaming Liu; Yang Xiao; Carlo Gualtieri; Huanfeng Duan; Jieqing Liu; Jian Zhou (Journal of Hydrology, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

Biomimetic tactile sensor for dynamic-static perception based on piezoionic and piezoresistive effects - Huanyu Liu; Jiaming Fan; Yongqi Kuang; Jing Xu; Qizhao Liang; Zhimeng Liu; Jun-Wei Zha; Yunhui Wu (Chemical Engineering Journal, 2026)

QACO: An adaptive multi-phase ant colony optimization approach for robust feature selection - Zihang Wang; Ye Liang; Wenwei Sun; Jiaming Liu (Swarm and Evolutionary Computation, 2026)

Heterogeneous distribution of salinity and nitrogen in the root-zone influence nitrogen harvest index and natural 15N abundance of tomato - Jinjing Liu; Zhenchang Wang; Yuexiong Wang; Yaosheng Wang; Yousef Alhaj Hamoud; Cheng Hong; Hiba Shaghaleh; Rangjian Qiu; Jiaming You; Minghao Tian; Kexin Chen; Xiaoman Qiang; et al. (Plant Science, 2026)

Multifactorial synergistic strategies mediate the biocontrol of Fusarium oxysporum-induced root rot by Bacillus velezensis SYL-3 - He Liu; He Huang; Yuzhe Wang; Mengnan An; Jiaming Bai; Jianquan Zhou; Haiyang Lan; Aiwei Qi; Baoan Song; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Metformin drives the antibiotic resistome in activated sludge by reshaping microbial communities and promoting horizontal gene transfer - Jiaming Yi; Zhengtao Li; Xuezhu Han; Jingpeng Li; Haotian Liu; Lin Zhu; Meizhen Wang (Journal of Hazardous Materials, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Chemical constituents of Baeckea frutescens L. and their chemotaxonomic significance - Haijun Wang; Jing Wang; Chunyu Fu; Jiafeng Wang; Lei Liu; Jiaming Wang (Biochemical Systematics and Ecology, 2026)

Research on the mining pressure law of gob-side roadway under the influence of fault tectonic zones and hard roofs - Junfeng Pan; Jiting Liu; Yubing Huang; Jiaming Gao; Yucheng Wang (Bulletin of Engineering Geology and the Environment, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

High-precision mapping of aquaculture ponds based on multi-feature fusion, using Sentinel-1 and Sentinel-2 time series images - Jie Wang; Shengqi Wang; Xun Wang; Jiaming Liu (International Journal of Remote Sensing, 2025)

Analysis of large deformation characteristics of deep foundation pit at a subway station constructed by the tunnel-before-station method - Jiaming Liang; Wenji Su; Tingjin Liu; Huifeng Wu; Lele Lu; Huashan Zhong; Shuyang Zhou (European Journal of Environmental and Civil Engineering, 2025)

Integrated improved ant colony optimization and Q-learning for ice navigation route planning - Jiaming Zhou; Xiuwen Liu; Hongshuai Xie; Yong Yin (Ocean Engineering, 2025)

Nonlinear relationship between built environment and commute mode choice: A comparison of commuters within and beyond the long commute threshold - Ming Yu; Zhaomin Tong; Jiaming Yang; Yanchi Lu; Yang Liu; Yanfang Liu; Yaolin Liu (Journal of Transport Geography, 2025)

Ionic liquid-derived fluorine doped high entropy metal oxides as efficient electrocatalysts for sulfion valorization - Longmei Shi; Anshuang Wu; Shengyun Xu; Jinbiao Liang; Shucan Qin; Jiaming Mao; Yanrong Liu; Yunqian Ma (Journal of Environmental Chemical Engineering, 2025)

The effect of hydroxyl groups and humidity on the adsorption capacity of amine-functionalized macroporous resins for direct air capture - Jiaming Wang; Xiaohan Weng; Tao Han; Yongqiang Wang; Jinning Yang; Chao Zhou; Dong Xu; Liying Liu (Chemical Engineering Journal, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Can we improve well‐being while reducing carbon emissions? Household‐level evidence from China - Jiaming Yu; Wenling Liu; Xiaoyan Meng; Xinzhu Zheng (Journal of Industrial Ecology, 2025)
Understanding the link between well‐being and carbon emissions is crucial, as demand‐side emission reduction efforts should not compromise living standards. While a nonlinear, threshold‐based relationship between well‐being and carbon emissions has been identified at the national level, empirical evidence at the household or individual level remains limited. Using data from the China Family Panel Studies, this study develops a multidimensional indicator framework to measure household well‐being and empirically assesses its relationship with per capita carbon emissions. The results indicate an inverted U‐shaped relationship, where carbon emissions are initially associated with improvements in well‐being. However, beyond a certain threshold, further increases in carbon emissions are no longer linked to significant gains in well‐being. Specifically, the decoupling threshold is estimated at 15.4 tons of CO 2 annually per capita in the absence of technological progress, and is reduced to 9.7 tons when technological improvements are taken into account. However, the available carbon budget is insufficient for all individuals to reach these decoupling points, and sample households could only reduce emissions by 1.4% without sacrificing overall well‐being. Moreover, prioritizing limited carbon allowances for low‐income groups may maximize societal well‐being, since their carbon intensity of human well‐being is comparatively lower. These findings underscore the importance of technological progress and population heterogeneity in designing fair and effective policies that balance well‐being with emission reductions.

Unveiling spatiotemporal patterns of urban ecosystem services flows in urban thermal environments: Insights from residency, age, and gender disparities - Jiaming Yang; Zhaomin Tong; Yaolin Liu; Yanfang Liu; Jiwei Xu; Yanchi Lu; Yifan Xie; Yang liu (Sustainable Cities and Society, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

Response of bacterial pathogens to process upgrades and floc sizes in a full-scale landfill leachate treatment plant - Binbin Sheng; Shitong Liu; Kenan Xiong; Jiaming Liu; Shuang Zhu; Haipeng Zhang; Rongxin Zhang (Journal of Environmental Management, 2025)

Energy analysis and microfracture characteristics of granite under dynamic modes I and II loading based on image processing techniques - Zida Liu; Zong-Xian Zhang; Quanqi Zhu; Peng Xiao; Jiaming Yang; Diyuan Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Enhancing phyto-microbial remediation of petroleum-contaminated soil using sophorolipid-modified biochar: Metagenomic and metabolomic insights - Yuhang Chen; Fumei Wang; Jiaqi Gao; Qinglong Liu; Jiaming Guo; Huan Liu (Environmental Research, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Direct electrospinning of super fatigue resistant and fire-retardant aerogels for thermal insulation - Lingyun Wu; Jiaming Li; Yunfang Liu; Manxi Zhou; Dan Xue; Gang Bai; Aosong Zhou; Xiaoping Yang; Gang Sui (Chemical Engineering Journal, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Digital simulation of condensation and water loss in ventilated lychee packaging - Jicheng Lin; Xiaodan Zhang; Yihong Jiang; Dongfeng Liu; Wei Cai; Guopeng Lin; Zhiwu Ding; Enli Lü; Jiaming Guo (Biosystems Engineering, 2025)

Experimental research on mechanised strip application process based on DEM of compressed granulated straw - Guibin Chen; Jiaming Yang; Fuzeng Yang; Qingjie Wang; Zhijie Liu; Zhengdao Liu (Biosystems Engineering, 2025)

Floodplain hydrodynamics and connectivity in a natural compound channel during unsteady flow events - Jiaming Liu; Yang Xiao; Saiyu Yuan; Taotao Zhang; Qingwei Lin; Kang Yuan; Ruiqi Wang; Carlo Gualtieri (Journal of Hydrology, 2025)

Synthesis of ultrafine boehmite from waste coal fly ash by integrating sol-gel process with sodium aluminate decomposition and hydrothermal treatment - Shuwei Lan; Zhaowen Wang; Qianhan Zhao; Zhibo Liu; Jiaming Li (Journal of Environmental Chemical Engineering, 2025)

Recycling waste poly(ethylene terephthalate) to prepare a Zn–MOF and its application as a nucleating agent for plastics and antibacterial agent on cotton fabrics - Xiaohui Lin; Jiaming Xu; Guoliang Sun; Jingjing Sun; Yi Xiao; Yanling Hu; Jinqing Yang; Yubiao Liao; Jianchun Liu; Mingyi Shang; Kun Wu (Journal of Environmental Chemical Engineering, 2025)

Mechanochemical treatment and valorization of hazardous fluorine from aluminum electrolyte in spent carbon anodes - Zhibo Liu; Zhenkun He; Bingqing Liu; Wenju Tao; Jiaxin Yang; Jiaming Li; Xianwei Hu; Zhaowen Wang (Journal of Environmental Chemical Engineering, 2025)

Exploring the functional diversity of wild Saccharomyces cerevisiae strains for breadmaking applications - Chenwei Pan; Jiaming Li; Tianzhi Qu; Hui Liu; Weiming Xiao; Bo Chen; Anqi Chen; Jian Chen (Food Bioscience, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Enhancing vessel trajectory prediction with bi-state space and squeeze excitation attention - Caiquan Xiong; Jiaming Li; Xinyun Wu; Donghua Liu; Qi Wang; Rong Gao; Jinjia Ruan (Ocean Engineering, 2025)

Construction of biochar-zeolite composite for enhanced VOCs adsorption: Interfacial reinforcement and steam-driven synergistic regulation of pore formation and dealumination - Dingcheng Liang; Yajie Chang; Peipei Zhang; Yuan Liu; Chenhong Luo; Zhijun Zhang; Qiang Xie; Jiaming Liang; Kangzhou Wang; Xiao Yang; Qingping Chen; Zhucan Xie; et al. (Journal of Cleaner Production, 2025)

Neuroprotective effects of Yangming-Kaixin-Yizhi formula in Alzheimer’s disease: dual regulation of PI3K/Akt and p38 MAPK signaling via network pharmacology and experimental approaches - Jing Lei; Jiaming Li; Wei Wu; Rui Xiong; Yao Liu; Yong Tang (Metabolic Brain Disease, 2025)

Towards efficient in situ gas thermal desorption remediation assisted with cross-borehole resistivity tomography - Teng Xia; Jiaming Zhang; Miao Li; Shupeng Li; Lili Guo; Peng Liu; Dixiang Wang; Deqiang Mao (Water Research, 2025)

Efficient separation and recycling of waste wind turbine blades through in-situ generation of peroxyacetic acid - Xinyi Xu; Jiaming Liu; Jiachun Feng; Bin Chen; Shiwen Gong; Xueer Ouyang; Changxu Qin; Gang Luo; Shicheng Zhang (Resources, Conservation and Recycling, 2025)

Highly selective aerobic oxidation of polystyrene to benzoic acid catalyzed by nitrogen dioxide - Yunkai Yu; Yue Zhu; Jiaming Liu; Minghao Zhang; Jing Li; Shicheng Zhang; Qingqing Mei (Science Bulletin, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Study on membrane electrolysis for the removal of Fe from the leachate of coal fly ash - Shuwei Lan; Youjian Yang; Zhaowen Wang; Yanchen Zheng; Jiaming Li; Qianhan Zhao; Tingting Liu (Journal of Environmental Chemical Engineering, 2025)

Decolorization and COD Removal of Direct Sunlight-resistant Black G Dye Wastewater Using Fe/Al-C Micro-electrolysis - Pengyu Liu; Binguo Yang; Jiaming Yan; Xiaojie Chen (Water, Air, & Soil Pollution, 2025)

Purification and characterization of cellulase produced by Bacillus sp. HMM - Lanqian Huang; Lei Mo; Jiaming Jiang; Yu Huo; Shisong Yu; Jianmei Ou; Siyu Liu; Xinyu Xie; Guyu Yan; Chuzun Liao; Shangxin Wu; Huiqing Zhang; et al. (Antonie van Leeuwenhoek, 2025)

Dynamic response of seabed in wind power of deep-shallow sea induced by internal solitary waves - Jiaming Xiang; Zhuangcai Tian; Youkou Dong; Enjin Zhao; Lei Song; Jianhua Yue; Guoqing Zhou; Xiaolei Liu; Xiujun Guo; Yonggang Jia (Marine Georesources & Geotechnology, 2025)

Insight of multi-polarization effect by constructing high-entropy spinel ferrite/perovskite @ amorphous carbon for enhancing electromagnetic wave absorption - Xinyang Liu; Zhekai Zhang; Fengyu Wu; Fenyang Tian; Jie Sheng; Menggang Li; Jiaming Li; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2025)

3D printing programmed diagnostic and therapeutic bioactive “all-in-one” microspheres with multistimuli responsiveness for cartilage regeneration - Feifei Zhou; Wenjing Zhang; Yuan Yang; Shuyu Liu; Jing Long; Siqi Zhang; Jiaming Cui; Yuxiao Lai; Weimin Zhu (Chemical Engineering Journal, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

Nutrient dynamics in the East China Sea: Seasonal changes, budget, and ecological impacts - Xiaosong Zhong; Jiaming Liu; Mengjiao Shi; Xiaotian Liu; Zongqing Lv; Xiangbin Ran (Progress in Oceanography, 2025)

Study on hot spot stress distribution and fatigue life assessment of KK-type cast steel nodes based on scaled model test - Haihan Jiao; Jiaming Liu; Lu Xu; Feng Shi; Hui Jin; Yongchun Fan (Ocean Engineering, 2025)

Phytoextraction of Soil Cadmium by Vetiveria zizanioides Dead Shoots - Wenwen Li; Ning Liu; Xiaoling Tan; Ruoyao Shen; Jiaming Yu; Jie Li; Khateeb Hussain; Shiyong Yang (Bulletin of Environmental Contamination and Toxicology, 2025)

Ceramic ultrafiltration membrane as pretreatment for drinking water nanofiltration treatment: Performance, cleaning, and costs based on an engineering case - Yawei Xie; Chengyue Fan; Yichen Fang; Xiwang Zhu; Jiaming Yan; Haodong Liu; Hongyuan Liu (Journal of Cleaner Production, 2025)

Near-white light-emitting copper nanoclusters/starch composites for multiplexing imaging and multichannel enhancement of latent fingerprints - Zhibo Gao; Chuanjun Yuan; Ming Li; Zhize Xu; Meng Wang; Jiaming Lyu; Shiqiang Sun; Fenghe Liu; Peiliang Han (Chemical Engineering Journal, 2025)

Enhanced carbon dioxide capture via amphiphobic PVDF membrane modification for membrane contactors: Overcoming wettability challenges - Chang Li; Yanbin Yun; Fengguang Huang; Jiaming Mao; Jia Liu; Wenjuan Yang; Chunyun Zhou; Meng Li (Chemical Engineering Journal, 2025)

One-dimensional LATP nanofiber reinforced PEO solid composite electrolyte for all-solid-state lithium-ion batteries with excellent cycling performance - Yudi Guo; Erqing Zhao; Weifang Su; Zhe Liu; Jiaming Li (Chemical Engineering Journal, 2025)

Anhydrous deep eutectic solvents-based biphasic absorbents for efficient CO2 capture: Unravelling the critical role of hydrogen bond-mediated electron transfer - Jiaming Mao; Yunqian Ma; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Chunyun Zhou; Hongwei Xie; Yanbin Yun (Chemical Engineering Journal, 2025)

Design and interaction dynamics analysis of a novel hybrid bending-twisting-pulling end-effector for robotic tomato picking - Jiaming Fang; Nianzu Dai; Zhenbo Xin; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2025)

Interface catalysis over AlPO4/Al2O3 with F-Al-O species for resource utilization of hydrofluorocarbon greenhouse gas - Yiwei Sun; Xiaoli Wei; Fangcao Liu; Bing Liu; Jiaming Zhao; Yubao Bi; Wenfeng Han (Journal of Environmental Chemical Engineering, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Interaction between imidacloprid residues in maize rhizospheric soil and soil nematode community - Jiaming Zhang; Yue Wu; Jiayi Liu; Xinru Wang; Weijia Pang; Juan Hua; Shihong Luo (Pesticide Biochemistry and Physiology, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

Leveraging machine learning to explore nonlinear associations between urban heat vulnerability and morbidity risk - Jiaming Yang; Zhaomin Tong; Jiwei Xu; Rui An; Yanfang Liu; Yaolin Liu (Urban Climate, 2025)

Development of dual polymerase spiral reaction for detection of Listeria monocytogenes and Staphylococcus aureus simultaneously - Moran Zhang; Hongzhou Chen; Jiaming Huang; Yongjin Dai; Yujuan Liu; Xiyao Zhou; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (International Journal of Food Microbiology, 2025)

A functional fluorine (F)-containing oxidiser of nano-networked NH4CuF3 to improve the combustion efficiency of Al powder - Xiandie Zhang; Haozhe Li; Xuxu Cui; Weiduo Fei; Xinwen Ma; Jiaming Liu; Pingyun Li; Xiaode Guo; Xiang Zhou (Fuel, 2025)

Overcoming carbon deposition in non-thermal plasma catalyzed biomass tar reforming: Innovative strategies employed by GPPC systems - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Yiqiang Liu; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Guilin Piao (Fuel, 2025)

Tracking Cr(VI) removal with spectral induced polarization under ZVI and AC synergetic remediation - Xinmin Ma; Jiaming Zhang; Chen Chao; Shiliang Liu; Khalil Ur Rahman; Shupeng Li; Lili Guo; Deqiang Mao (Environmental Research, 2025)

Safety control of blasting vibration in new tunnel excavation adjacent to existing tunnel - Junru Zhang; Zhijian Yan; Jianchi Ma; Qihua Deng; Jiaming Liu; Jimeng Feng; Zhiyong Wang (Bulletin of Engineering Geology and the Environment, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Excessive nitrogen application reduces eating quality by changing the starch molecular structure and physicochemical properties of inferior grains - Can Zhao; Yue Chen; Kunlun Liu; Guangming Liu; Jiaming Lu; Weiling Wang; Zhongyang Huo (Journal of Cereal Science, 2025)

Enhanced steam reforming of benzene in a two-stage catalytic system: Insights into metal synergies and carbon deposition evolution - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Yuan Sun (Fuel, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Haversian bone mimicking scaffold with built-in vasculature for bone tissue engineering - Jian Liu; Zhen You; Xinmei Li; Boyang Zhang; Jiaming Sun; Zhenxing Wang (Chemical Engineering Journal, 2025)

Acoustic micromixing in a serpentine channel with sharp teeth for controllable nanomaterial synthesis - Bin Ran; Bo Liu; Chaozhan Chen; Wenqiang Tong; Jiaming Shi; Jiaxi Du; Zhihang Yu; Siwei Bai; Huaying Chen; Yonggang Zhu (Chemical Engineering Journal, 2025)

Study on strength and reduction characteristics of iron ore powder-green carbon composite briquettes - Yifan Chai; Shijie Wang; Jiaming Zhang; Yanshuo Shi; Peijun Liu; Shengli An; Chuan Wang; Xiaojun Ning (Fuel, 2024)

Constitutive modelling of the shakedown response of sensitive clay to undrained long-term cyclic loads incorporating structural destruction - Jiaming Liu; Chuang Zhao; Hongming Liu; Xuecheng Bian; Yunmin Chen (Computers and Geotechnics, 2024)

Environmentally friendly recycling of energy storage functional materials from hazardous waste lithium-containing aluminum electrolytes - Jiaxin Yang; Wenju Tao; Jiaming Li; Lingyu Kong; Shaohua Wu; Jingui He; Zhaoshun Liu; Yu Sun; Chao Fan; Zhaowen Wang (Chemical Engineering Journal, 2024)

Lotus rhizome-inspired superhydrophobic capillarity mesh surface for long-term plastron stability - Jiaming Wang; Yuhong Liu (Chemical Engineering Journal, 2024)

Microbial community dynamics in different floc size aggregates during nitrogen removal process upgrading in a full-scale landfill leachate treatment plant - Binbin Sheng; Shitong Liu; Kenan Xiong; Jiaming Liu; Shuang Zhu; Rongxin Zhang (Bioresource Technology, 2024)

Spatial Patterns and Drivers of Intelligent Manufacturing from a ‘Global-local’ Perspective: A Study of China’s Industrial Robotics - Fengjiao Li; Hong Zhang; Lili Jiang; Jiaming Liu (Chinese Geographical Science, 2024)

Influence of staggered guide vane on hydraulic performance of reactor coolant pump - Binhao Liu; Daoxing Ye; Junlin Chen; Mengke Wu; Rui Deng; Junyu Zhang; Jiaming Han (Annals of Nuclear Energy, 2024)

Fleet availability analysis and prediction for shared e-scooters: An energy perspective - Jiahui Zhao; Jiaming Wu; Sunney Fotedar; Zhibin Li; Pan Liu (Transportation Research Part D: Transport and Environment, 2024)

Nano ZnO modified amorphous carbon materials enabling long-cycle performance and high-capacity for lithium/sodium-ion batteries - Jiaming Liu; Zhen He; Tongfa Zhao; Yuqian Wei; lingpei Hou; Yunfei Song; Yuxin Wang (Chemical Engineering Journal, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

3MSP2: Sequential picking planning for multi-fruit congregated tomato harvesting in multi-clusters environment based on multi-views - Nianzu Dai; Jiaming Fang; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2024)

Transport processes of dissolved and particulate nitrogen and phosphorus over urban road surface during rainfall runoff - Yang Xiao; Chi Zhang; Taotao Zhang; Bin Luan; Jiaming Liu; Qiang Zhou; Chentao Li; Haoke Cheng (Science of The Total Environment, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

ILP1 and NTR1 affect the stability of U6 snRNA during spliceosome complex disassembly in Arabidopsis - Jiaming Wu; Wei Chen; Shengchao Ge; Xueliang Liu; Junling Shan; Meishan Zhang; Yuan Su; Yunfeng Liu (Plant Science, 2024)

Optimal classification of radiant time series for cooling load calculation of building air-conditioning systems - Jing Ren; Youming Chen; Xinchao Zhang; Jiaming Liu (Energy and Buildings, 2024)

A hybrid PM2.5 interval concentration prediction framework based on multi-factor interval decomposition reconstruction strategy and attention mechanism - Jiaming Zhu; Lili Niu; Peng Zheng; Huayou Chen; Jinpei Liu (Atmospheric Environment, 2024)

Numerical research on the influence of ocean conditions on the transient response of passive decay heat removal system of the floating Fluoride-Salt-Cooled High-Temperature Reactors - Limin Liu; Ziyin Liu; Jiaming Zhang; Cong Shen; Maolong Liu; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2024)

Enhanced reductive degradation of trichloroethylene by ball milled nitridation of bimetallic Ni-ZVI: Combination effect of electron transfer and catalytic hydrogenation - Yinghao Shi; Dong Wang; Jiaming Guo; Feilong Gao; Linan Liu; Jingchun Tang (Journal of Cleaner Production, 2024)

Kinematic Stability Analysis of Anchor Cable Structures in Submerged Floating Tunnel under Combined Parametric–Vortex Excitation - Jiaming Xiong; Song Sang; Youwei Du; Chaojie Gan; Ao Zhang; Fugang Liu (Journal of Marine Science and Engineering, 2024)
The submerged floating tunnel is a marine transportation infrastructure that links two shorelines. The tunnel tube body’s buoyancy exceeds gravity, with anchoring ensuring equilibrium. Anchoring reliability is crucial. This study presents a three-way coupled kinematic model for the mooring structure, formulated on Hamilton’s principle and Kirchhoff’s assumption. It explores the impact of the tube body’s buoyancy-to-weight ratio and the sea current’s angle of incidence on mooring motion response. By solving the motion analysis model, Hill’s equation system is derived to assess the parameter instability of the anchor cable structure. The coefficient of excitation instability intervals for the submerged floating tunnel is determined and validated. The findings indicate the following: (1) Increasing the float-weight ratio reduces displacement response amplitudes in all directions, bringing downstream and transverse currents closer to their initial positions; (2) Changes in current direction angles result in decreased downstream excitation strength and increased transverse displacement response with the same excitation direction; (3) The instability interval visualization effectively predicts anchor cable structure instability under parametric excitation. Structures within the instability region are deemed unstable, while those outside are considered stable.

LSGNet: A lightweight convolutional neural network model for tomato disease identification - Shengxian Yang; Licai Zhang; Jianwu Lin; Tomislav Cernava; Jitong Cai; Renyong Pan; Jiaming Liu; Xingtian Wen; Xiaoyulong Chen; Xin Zhang (Crop Protection, 2024)

Binary-Network structured PI@SiO2 nanofibrous composite aerogels with temperature invariant superelasticity for thermal insulation - Qicheng Xue; Nanxi Dong; Peiqi Fan; Daolei Lin; Guofeng Tian; Jun Liu; Jiaming Wei; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Contributions of China's terrestrial ecosystem carbon uptakes to offsetting CO2 emissions under different scenarios over 2001–2060 - Mengyang Xu; Ziyu Zhang; Chao Yue; Jie Zhao; Pengyi Zhang; Mengyu Wang; Jiaming Wang; Hongfei Zhao; Jinyue Liu; Xianhui Tang; Junhao He (Global and Planetary Change, 2024)

Experimental and theoretical investigation of an ionic liquid-based biphasic solvent for post-combustion CO2 Capture: Breaking through the “Trade-off” effect of viscosity and loading - Jiaming Mao; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Yanbin Yun; Guicheng Liu; Meng Li; Manxiang Wang (Chemical Engineering Journal, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Cryopreserved leukapheresis material can be transferred from controlled rate freezers to ultracold storage at warmer temperatures without affecting downstream CAR-T cell culture performance and in-vitro functionality - Jiaming Wei; Katherine Chaney; Woo Jin Shim; Heyu Chen; Grace Leonard; Sean O'Brien; Ziyan Liu; Jinlin Jiang; Robert Ulrey (Cryobiology, 2024)

Rab18 maintains homeostasis of subcutaneous adipose tissue to prevent obesity-induced metabolic disorders - Jiaming Liu; Liangkui Li; Dijin Xu; Yuqi Li; Tao Chen; Yeyang Liu; Yuqian Bao; Yan Wang; Longyan Yang; Peng Li; Li Xu (Science China Life Sciences, 2024)

Cooling and optimizing urban heat island based on a thermal knowledge-informed multi-type ant colony model - Zhaomin Tong; Jiaming Yang; Yaolin Liu; Ziyi Zhang; Sui Liu; Yanchi Lu; Bowen Pang; Rui An (Remote Sensing of Environment, 2024)

Comparative study on dynamic responses of integrated installation process of a 5-MW and a 15-MW offshore wind turbine considering a pre-installed foundation - Jiaming Liu; Zhongming Xiao; Kai Wang; Shuo Huang; Yu Du (Ocean Engineering, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

Mechanism study on the effect of heat shock on the functional characteristics of soybean protein isolate by regulating the change of endogenous enzyme activity in soybeans - Feng Yan; Shisheng Tong; Jiaming Zhang; Yuanyuan Zhao; Ping Liu (Food Hydrocolloids, 2024)

Clustering and optimization of nodes, beams and panels for cost-effective fabrication of free-form surfaces - Minghao Bi; Yuanpeng Liu; Tao Xu; Yunzhen He; Jiaming Ma; Zicheng Zhuang; Yi Min Xie (Engineering Structures, 2024)

Reduced moisture caused by short-term grazing prohibition results in a significant decrease of fungi abundance - Hongbin Zhao; Xiaofu Zhang; Huiyan Liu; Xue Bai; Jiaming Nie; Guodong Han; Bing Han (Journal of Arid Environments, 2024)

Aggregation, retention and transport of γ-MnO2 nanoparticles in water-saturated porous media: Impact on the immobility of thallium - Jiaming Luo; Dafeng Cai; Lezhang Wei; Hang Shi; Yu Liu; Haiqi Yan; Dinggui Luo; Tangfu Xiao; Xuexia Huang; Qihang Wu (Environmental Pollution, 2024)

Re-N-acetylation of group B Streptococcus type Ia capsular polysaccharide improves the immunogenicity of glycoconjugate vaccines - Jiaming Bei; Jianrong Wu; Jia Liu (Carbohydrate Polymers, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Hyporheic exchange in a compound channel under unsteady flow: Numerical simulations - Jiaming Liu; Yang Xiao; Pei Xin; Nairu Wang; Saiyu Yuan; Taotao Zhang; Chentao Li; Carlo Gualtieri (Journal of Hydrology, 2024)

Carbon emissions and low-carbon development in Olefin industry - Qun Shen; Jiaming Gu; Li Shang; Shuang Liu; Xuehang Song; Weisheng Yu; Yongping Liu; Nannan Sun; Wei Wei (Environmental Research, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Performance and membrane fouling characteristics of a drinking water multistage NF system based on membrane autopsy from a full-scale system - Chengyue Fan; Jiaming Yan; Haodong Liu; Yawei Xie; Hongyuan Liu (Journal of Water Process Engineering, 2024)

Characteristics and multi-factor mechanisms of dam construction on food web structure in cold-region rivers - Jiaming Hou; Qinghui Zeng; Peng Hu; Yunzhong Jiang; Yinglan A; Qin Yang; Baolong Zhao; Huan Liu; Zefan Yang; Xiaohui Qu (Journal of Hydrology, 2024)

Heterologous expression of protein-glutaminase in Escherichia coli Nissle 1917 for improved flavor properties of soy protein and its implications on high-moisture extrudates - Jiaming Li; Xinwen Zhang; Shijun Luo; Xinhong Wu; Guoqiang Zhang; Jianghua Li; Xiao Liu (Food Bioscience, 2024)

Effects of soybean endogenous enzyme hydrolysis on the quality of soymilk after blanching - Feng Yan; Shisheng Tong; Jiaming Zhang; Yuanyuan Zhao; Ping Liu (Food Bioscience, 2024)

Tailored amphiphilic polymers enable stabilized biologics in hyperthermal water and freeze-drying process - Xiaowen Liu; Jian Chen; Jiaming Zhong; Fener Chen (Chemical Engineering Journal, 2024)

Biphasic solvents based on dual-functionalized ionic liquid for enhanced post-combustion CO2 capture and corrosion inhibition during the absorption process - Jiaming Mao; Chang Li; Yanbin Yun; Jia Liu; Wenjuan Yang; Meng Li; Lihua Wang; Chunli Li; Wenli Liu (Chemical Engineering Journal, 2024)

Energetic characteristics of highly reactive Si nanoparticles prepared by magnesiothermic reduction of mesoporous SiO2 - Xinwen Ma; Weiduo Fei; Jiaming Liu; Xiandie Zhang; Jie Ji; Xiang Zhou (Chemical Engineering Journal, 2024)

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Rheological and tribological properties of high internal phase emulsions stabilized by pH-induced soy protein isolate-carrageenan complex coacervates - Fanjun Meng; Jiaming Li; Cong Yang; Miao Wang; Xiao Liu (Food Hydrocolloids, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Regional Modeling of the Lithospheric Magnetic Field from Local and Satellite Constraints: A Case Study of the Xinjiang Region - Yan Feng; Jiaxuan Zhang; Shengqing Xiong; JinYuan Zhang; Jiaming Ou; Shuang Liu; Yijun Li; Ya Huang (Pure and Applied Geophysics, 2023)

Investigation of Mechanical Properties of Quartz and Illite in Shale Using Molecular Dynamics Simulation - Shuang Liang; Mingyu Gao; Shuo Sun; Yikun Liu; Wanxin Li; Jingkun Wang; Jiaming Wang; Chengfeng Yin (Natural Resources Research, 2023)

Catalytic ozonation of multi-VOCs mixtures over Cr-based bimetallic oxides catalysts from simulated flue gas: Effects of NO/SO2/H2O - Peixi Liu; Hairong Tang; Jiaming Shao; Yong He; Yanqun Zhu; Elisabete C.B.A. Alegria; Zhihua Wang; Armando J.L. Pombeiro (Chemosphere, 2023)

A novel fish CRADD inhibits Singapore grouper iridovirus (SGIV) infection by mediating apoptosis and modulating SGIV CARD (VP48)-caspase-2 interaction - Xin Zhang; Siting Wu; Zetian Liu; Jiaming Liao; Jingguang Wei; Qiwei Qin (Aquaculture, 2023)

Spatiotemporal distribution of phytoplankton community structure and its relationship with environmental factors in Hongze Lake, China - Jiahui Shi; Lixiao Ni; Jiaming Liu; Chen Xu; Jianhua Zhang; Xuqing Chen (Urban Climate, 2023)

Insights into chloride sorption and phase transformation of the synthesized Ca-Al bimetallic oxides in flue gas desulfurization wastewater - Zhen Zhou; Qiaoling Zhu; Ziwei Lan; Yuyue Yang; Li Zeng; Chengrui Liu; Jiaming Guo; Xiaodan Zhao (Chemical Engineering Journal, 2023)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

A multi-scale experiment analysis of air entrainment and heat exhaust coefficient under lateral smoke exhaust in tunnel fires - Qiulin Liu; Zhisheng Xu; Chuangang Fan; Xiaochun Zhang; Jiaming Zhao; Houlin Ying; Haowen Tao (Tunnelling and Underground Space Technology, 2023)

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

Multi-objective shape optimization of autonomous underwater vehicle by coupling CFD simulation with genetic algorithm - Xiaodong Chen; Liang Yu; Leo Yang Liu; Lele Yang; Shunyuan Xu; Jiaming Wu (Ocean Engineering, 2023)

Abundance, characteristics and seasonal variation of microplastics in a domestic sewage treatment plant in Nanjing, China - Juan Huang; Jing Tuo; Luming Wang; Jiaming Liu (Journal of Water Process Engineering, 2023)

Zwitterionic loose polyamide nanofiltration membrane with good antifouling properties for efficient removal of humic acid and dyes - Chengbao Geng; Fangbo Zhao; Hongyan Niu; Jiaming Zhang; Yang Liu; Lijia Liu; Hongxing Dong; Zhiguo Li; Hongxu Chen (Journal of Environmental Chemical Engineering, 2023)

Extreme low-temperature events can alleviate micronutrient deficiencies while increasing potential health risks from heavy metals in rice - Min Kang; Xue Wang; Jiankun Chen; Qizhao Fang; Jiaming Liu; Liang Tang; Leilei Liu; Weixing Cao; Yan Zhu; Bing Liu (Environmental Pollution, 2023)

Catalytic degradation of bisphenol a (BPA) in water by immobilizing silver-loaded graphene oxide (GO-Ag) in ultrafiltration membrane with finger-like structure - Ye Yang; Fangbo Zhao; Liu Yang; Jiaming Zhang; Hee-Deung Park; Zhiguo Li; Hongxu Chen; Ximeng Zhang; Mingjin Gao (Chemical Engineering Journal, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Recent advances in sulfidized nanoscale zero-valent iron materials for environmental remediation and challenges - Wenjing Xue; Jun Li; Xinyu Chen; Hongdou Liu; Siqi Wen; Xiaoyu Shi; Jiaming Guo; Yang Gao; Jian Xu; Yiqun Xu (Environmental Science and Pollution Research, 2023)

An interval-valued carbon price forecasting method based on web search data and social media sentiment - Jinpei Liu; Xue Li; Piao Wang; Huayou Chen; Jiaming Zhu (Environmental Science and Pollution Research, 2023)

Abundance, characteristics, and removal of microplastics in different wastewater treatment plants in a Yangtze River Delta city of China - Juan Huang; Luming Wang; Jiaming Liu; Xiuwen Qian; Yufeng Wu (Journal of Water Process Engineering, 2023)

Study on calcareous sand treated by MICP in different NaCl concentrations - Jitong Zhao; Yi Shan; Huawei Tong; Jie Yuan; Jiaming Liu (European Journal of Environmental and Civil Engineering, 2023)

Performance and response of coupled microbial fuel cells for enhanced anaerobic treatment of azo dye wastewater with simultaneous recovery of electrical energy - Liming Hu; Na Liu; Chang Li; Jiaming Mao; Meng Li; Yanbin Yun; Wenli Liu (Environmental Science and Pollution Research, 2023)

Dynamic retention of thallium(I) on humic acid: Novel insights into the heterogeneous complexation ability and responsiveness - Wanpeng Chen; Xiaoliu Huangfu; Jiaming Xiong; Hongxia Liu; Qiang He (Water Research, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

Why the same economic reform leads to different urbanization route? --The comparative study of China and India - Jiaming Li; Ziyi Wang; Mingyi Liu (Land Use Policy, 2023)

Quality retention and delay postharvest senescence of figs (Ficus carica L.) using 1-methylcyclopropene and modified atmosphere packaging during cold storage - Cailian Wang; Jiaming Du; Dehua Hou; Xiaohong Guo; Qianting Liu; Linwen Liu; Yu Fang; Liping Kou (Food Bioscience, 2023)

Effect of gastrodin against cognitive impairment and neurodegeneration in APP/PS1 mice via regulating gut microbiota–gut–brain axis - Yuhe Zhang; Yan Chen; Shushu Yuan; Qingxia Yu; Jianjiong Fu; Luyun Chen; Jiaming Liu; Yuping He (Experimental Brain Research, 2023)

From black water to flushing water: potential applications of chlorine-mediated indirect electrooxidation for ammonia removal - Shanshan Liu; Longqian Xu; Xiaoqing Lin; Jiaming Zhang; Deli Wu (Environmental Science and Pollution Research, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Improving the prediction accuracy of small-strain shear modulus of granular soils through PSD: An investigation enabled by DEM and machine learning technique - Xingyang Liu; Zhanchao Li; Degao Zou; Linsong Sun; Khailah Ebrahim Yahya; Jiaming Liang (Computers and Geotechnics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Genomic Profiling of Lower-Grade Gliomas Subtype with Distinct Molecular and Clinicopathologic Characteristics via Altered DNA-Damage Repair Features - Aierpati Maimaiti; Yanwen Liu; Aimitaji Abulaiti; Xixian Wang; Zhaohai Feng; Jiaming Wang; Maimaitili Mijiti; Mirzat Turhon; Nilipaer Alimu; Yongxin Wang; Wenbao Liang; Lei Jiang; et al. (Journal of Molecular Neuroscience, 2023)

A data-driven support system for the efficient schedule delay management of the ultra-high-voltage projects considering subjective risk preferences - Yunna Wu; Jiaming He; Yijia Liao; Yao Tao; Fangtong Liu; Jianli Zhou (Sustainable Cities and Society, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Comparative analysis of husk microstructure, fruit quality and concentrations of bioactive compounds of different pomegranate cultivars during low temperature storage - Qianting Liu; Xiaohong Guo; Jiaming Du; Yidan Guo; Xiaocheng Guo; Liping Kou (Food Bioscience, 2023)

A conceptual model for the shakedown response of soft clay to high-cycle, low-amplitude undrained loading - Chuang Zhao; Jiaming Liu; Hongming Liu; Xuecheng Bian; Yunmin Chen (Computers and Geotechnics, 2023)

Antibacterial anodic aluminium oxide-copper coatings on aluminium alloys: preparation and long-term antibacterial performance - Jiahuan Chen; Zhen He; Jiaming Liu; Yuxin Wang; Michael Hodgson; Wei Gao (Chemical Engineering Journal, 2023)

Improving the detection accuracy of the nitrogen content of fresh tea leaves by combining FT-NIR with moisture removal method - Jiaming Guo; Han Huang; Xiaolong He; Jinwei Cai; Zhixiong Zeng; Chengying Ma; Enli Lü; Qunyu Shen; Yanhua Liu (Food Chemistry, 2023)

Effect of Se application on selenium accumulation and fruit quality in pear (Pyrus ussuriensis) - Chi Yuan; Haidong Bu; Jiaming Zhao; Jiaojiao Liu; Guobao Wang; Hui Yuan; Aide Wang (Acta Physiologiae Plantarum, 2023)

Self-repairing thermal energy storage gels demonstrating superior thermophysical properties and wearability towards personal thermal management in static and dynamic modes - Yingying Luo; Hongjiao Wu; Junpeng Qiao; Jiaming Zhang; Kai Liu; Liqing Zou; Ying Chen; Pengcheng Lin (Chemical Engineering Journal, 2023)

Highly efficient removal of hexavalent chromium from electroplating wastewater by ferrous/ferric hydroxide complex: From lab-scale to pilot-scale study - Xiaoqing Lin; Longqian Xu; Zhenyu Zhao; Shanshan Liu; Jiaming Zhang; Deli Wu (Chemical Engineering Journal, 2023)

Self-healing, reprocessable, degradable, thermadapt shape memory multifunctional polymers based on dynamic imine bonds and their application in nondestructively recyclable carbon fiber composites - Xiaohong Liu; Ending Zhang; Jiaming Liu; Jingjing Qin; Mengqin Wu; Chaolong Yang; Liyan Liang (Chemical Engineering Journal, 2023)

Adaptive neighbourhood recovery method for machine learning based 3D point cloud classification - Jiaming Xue; Chaoguang Men; Yongmei Liu; Shun Xiong (International Journal of Remote Sensing, 2023)

Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength - Yu Cao; Chengxue Ma; Jinni Yao; Wanpeng Chen; Li Gu; Hongxia Liu; Caihong Liu; Jiaming Xiong; Xiaoliu Huangfu (Chemosphere, 2023)

A sustainable development pattern integrating data centers and pasture-based agrivoltaic systems for ecologically fragile areas - Jiaming Zhang; Tao Wang; Yuan Chang; Bingsheng Liu (Resources, Conservation and Recycling, 2023)

Analysis and intervention of heatwave related economic loss: Comprehensive insights from supply, demand, and public expenditure into the relationship between the influencing factors - Peng Wang; Wendi Zhang; Jiawen Liu; Pan He; Jiaming Wang; Lei Huang; Bing Zhang (Journal of Environmental Management, 2023)

Hydrogenation of biomass pyrolysis oil using enhanced reduction catalytic capacity cellular by expressing excavated carbonyl reductase - Chongyang Bu; Hui Qiao; Lihua Zou; Yuanming Tao; Jiaming Fu; Chao Liu; Zhaojuan Zheng; Jia Ouyang (Fuel, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Mechanisms of PiT2-loop7 Missense Mutations Induced Pi Dyshomeostasis - Hao Sun; Xuan Xu; Junyu Luo; Tingbin Ma; Jiaming Cui; Mugen Liu; Bo Xiong; Shujia Zhu; Jing-Yu Liu (Neuroscience Bulletin, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

TP-DDI: A Two-Pathway Deep Neural Network for Drug–Drug Interaction Prediction - Jiang Xie; Chang Zhao; Jiaming Ouyang; Hongjian He; Dingkai Huang; Mengjiao Liu; Jiao Wang; Wenjun Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Differential patterns and assembly processes of bacterial communities from distinct microhabitats in a subtropical estuary - Kang Ma; Ze Ren; Jiaming Ma; Nannan Chen; Jingling Liu (Frontiers in Marine Science, 2022)
Estuarine ecosystems interconnect freshwater and marine environments, and comprise multiple highly dynamic and complex microhabitats. The resident microbiota in estuary is influenced by contrasting microenvironmental heterogeneity. However, the bacterial patterns and assembly processes in different microhabitats of estuarine ecosystem are not well studied. Here, we investigated the bacterial diversity, functions and community assembly mechanisms of mangrove soil, river sediment and overlying water in a subtropical estuary. Results showed that similar profiles of bacterial communities existed in the mangrove soil and river sediment and were dominated by Proteobacteria, Bacteroidetes and Acidobacteria. In terms of different microhabitats, the lowest alpha diversity of bacterial communities was found in overlying water and were dominated by Proteobacteria, Actinobacteria and Bacteroidetes. Meanwhile, the functional potential genes associated with carbon metabolisms were also substantially different in the three microhabitats. The relative abundance of genes connected to aerobic carbon respiration was significantly higher in overlying water than in the other two microhabitats. Bacterial communities in river sediments were enriched for genes associated with aerobic methane oxidation. The strong environmental heterogeneity of the three nearby microhabitats shaped the taxonomic and functional composition of the bacterial communities in estuarine ecosystem. Moreover, the plant rhizosphere effect increased the proportion of the dispersal limitation processes in mangrove soils compared to that in river sediments, while the overlying water was fluid and had less environmental selection processes compared to that in mangrove soil and river sediment. The bacterial communities in river sediment construct a more clustered network, while the overlying water network showed the highest complexity. Our findings reveal the differences of bacterial patterns and community assembly mechanisms in distinct microhabitats of estuarine ecosystems, and provide important insights for a comprehensive understanding of the mechanisms to maintain estuarine wetland conservation under environmental changes.

The Impact of Scour on Laterally Loaded Piles Bored and Socketed in Marine Clay - Chentao Li; Yang Xiao; Jieqing Liu; Qingwei Lin; Taotao Zhang; Jiaming Liu (Journal of Marine Science and Engineering, 2022)
The majority of long-span bridges and offshore construction in deep water are supported by bored pile foundations. Pile foundations under water will be susceptible to scour, which will pose a significant danger to their safe operation. A three-dimensional finite element (FE) numerical analysis was conducted to examine the influence of scour on the responses of laterally loaded drilled piles in marine clays. First, the FE numerical model was calibrated using field test data of a drilled pile that did not include scour in soft marine clay. The findings of numerical modeling reveal that scour decreases the ultimate lateral capacity of socketed drilled piles, with the percentage of reduction being strongly related to scour types and depth, but moderately related to scour hole width and slope angle. Finally, a semi-empirical formula for calculating the effects of scour on the lateral capacity of socketed drilled piles following scour is presented. This method may be utilized fast and effectively to calculate scour’s effects.

Short-chain fatty acids-producing probiotics: A novel source of psychobiotics - Yiwen Cheng; Jiaming Liu; Zongxin Ling (Critical Reviews in Food Science and Nutrition, 2022)

Effects of nitrogen addition on soil faunal abundance: A global meta‐analysis - Junxi Hu; Shixing Zhou; Liehua Tie; Xiong Liu; Xing Liu; Anjiu Zhao; Jiaming Lai; Lin Xiao; Chengming You; Congde Huang (Global Ecology and Biogeography, 2022)
Aim Soil fauna has a wide range of ecosystem functions. Anthropogenic atmospheric nitrogen (N) deposition affects the structure and function of soil fauna by changing the microenvironment and resources. Given that soil faunal responses can vary considerably among taxonomic groups, N deposition rate, and ecosystems, however, there is little consensus. We aimed to evaluate the effects of N deposition on different soil faunal taxa across different terrestrial ecosystems. Location Global. Time period 1970–2021. Major taxa studied Soil fauna. Methods We conducted a meta‐analysis that yielded 264 observations from 43 publications. We evaluated the responses to N addition of soil faunal abundance for three different taxa (nematodes, mites, collembolans) in three ecosystem types (cropland, forest, and grassland). Results Our results showed an overall negative effect of N addition on soil fauna. However, the effect varied among soil faunal taxa. Specifically, N addition had no significant effects on the abundance of collembolans and mites in any ecosystem. On the other hand, N addition significantly reduced the abundance of all nematode trophic groups except bacterivores. The overall reduction of soil fauna is likely driven by the nematode response. The negative effects of N addition on nematode abundance were contingent on the N addition rate, N addition form, and ecosystem type. N addition decreased nematode abundance at N addition rates of more than 100 kg/ha/year. Inorganic N addition negatively affected nematode abundance. Finally, N addition had a greater adverse effect on nematodes in cropland and grassland compared to forest ecosystems. Main conclusions Our results demonstrate the overall negative effects of N addition on nematode abundance. Excessive N addition should be avoided in cropland and grassland management. Further, we suggest the application of organic fertilizer instead of inorganic fertilizer to minimize the N‐induced negative effects on soil nematodes.

Ultrasonic-assisted synthesis of highly stable RuPd bimetallic catalysts supported on MgAl-layered double hydroxide for N-ethylcarbazole hydrogenation - Xiaoran Liu; Jiaming Shi; Xuefeng Bai; Wei Wu (Environmental Science and Pollution Research, 2022)

Lack of Knowledge, the main Stumbling Block of Fertility Preservation Promotion in China - Meng Wang; Lixia Zhu; Hua Xiong; Jiaming Wang; Zhou Li; Liu Yang; Lei Jin; Qingsong Xi (Journal of Cancer Education, 2022)

Genome-wide genetic diversity and IBD analysis reveals historic dissemination routes of pear in China - Xuening Chen; Mingyue Zhang; Manyi Sun; Yueyuan Liu; Shengnan Li; Bobo Song; Mengyan Li; Shaoling Zhang; Runze Wang; Jiaming Li; Kejiao Zhao; Jun Wu (Tree Genetics & Genomes, 2022)

Discovery of the Early Paleozoic Akechukesai high-Mg diorites in the western segment of East Kunlun Orogenic Belt and its constraints on the mechanism of break-off from Proto-Tethys oceanic subducted slab - Chao Wang; Fengyue Sun; Dongwei Liu; Lei Zuo; Tuofei Zhao; Jiaming Yan (Geosciences Journal, 2022)

Tilt deformation and instability of the slope for predicting rainfall-induced landslide - Handong Liu; Jing-jing Liu; Jiaxing Chen; Jiaming Luo; Wei Guo (Arabian Journal of Geosciences, 2022)

HIV Tat Protein Induces Myocardial Fibrosis Through TGF-β1-CTGF Signaling Cascade: A Potential Mechanism of HIV Infection-Related Cardiac Manifestations - Yannan Jiang; Lu Chai; Hongguang Wang; Xiuyun Shen; Moyondafoluwa Blessing Fasae; Jinfeng Jiao; Yahan Yu; Jiaming Ju; Bing Liu; Yunlong Bai (Cardiovascular Toxicology, 2021)

Single-stranded DNA generated by high temperature accepts protons and builds up mutagenic and carcinogenic strong acids - Yuhan Lin; Xiaoxiao Zhang; Yuchuan Wang; Jiaming Zhang; Qiuyun Liu (Molecular Biology Reports, 2021)

Diverse transcriptional patterns of homoeologous recombinant transcripts in triploid fish (Cyprinidae) - Li Ren; Xueyin Zhang; Jiaming Li; Xiaojing Yan; Xin Gao; Jialin Cui; Chenchen Tang; Shaojun Liu (Science China Life Sciences, 2021)

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Effects of High-Dose of Copper Amino Acid Complex on Laying Performance, Hematological and Biochemical Parameters, Organ Index, and Histopathology in Laying Hens - Qin Zhou; Jiaming Zhu; Bing Liu; Jialing Qiu; Xintao Lu; Brian Curtin; Fei Ji; Dongyou Yu (Biological Trace Element Research, 2021)

Gene polymorphism of chalcone isomerase influence the accumulation of flavonoids in licorice (Glycyrrhiza spp.) - Xiaodong Zhang; Shaokai Tian; Lin Qi; Wendong Li; Jiaming Hou; Lin Yang; Zhixin Zhang; Ying Liu (Genetic Resources and Crop Evolution, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Development and characterization of 33 SNP markers for the red-crowned crane (Grus japonensis) using a genotyping-by-sequencing approach - Nan Xu; Yining Chen; Jiaming Zhang; Qingzheng Zhang; Jing Yang; Jingjing Li; Hongyi Liu (Conservation Genetics Resources, 2020)

Preliminary marine gravity field from HY-2A/GM altimeter data - Qiankun Liu; Ke Xu; Maofei Jiang; Jiaming Wang (Acta Oceanologica Sinica, 2020)

Oxidative Damage Induced by Nano-titanium Dioxide in Rats and Mice: a Systematic Review and Meta-analysis - Hongmei An; Chunmei Ling; Mengchuan Xu; Mingjuan Hu; Haixia Wang; Jiaqing Liu; Guangling Song; Jiaming Liu (Biological Trace Element Research, 2020)

Important progress and future prospects for studies on urban public recreational space in China - Ling Yu; Jiaming Liu; Tao Li (Journal of Geographical Sciences, 2019)

Analysis of deformation characteristics for a reservoir landslide before and after impoundment by multiple D-InSAR observations at Jinshajiang River, China - Lingjing Li; Xin Yao; Jiaming Yao; Zhenkai Zhou; Xin Feng; Xinghong Liu (Natural Hazards, 2019)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Stacked auto-encoder for classification of polarimetric SAR images based on scattering energy - Ronghua Shang; Yongkun Liu; Jiaming Wang; Licheng Jiao; Rustam Stolkin (International Journal of Remote Sensing, 2019)

Optimum removal conditions of aniline compounds in simulated wastewater by laccase from white-rot fungi - Bo Yang; Yacheng Wang; Zhiguo Liu; Jun Liu; Jiaming Cai (Journal of Environmental Health Science and Engineering, 2019)

Preparation of chitosan/Co-Fe-layered double hydroxides and its performance for removing 2,4-dichlorophenol - Bo Yang; Jun Liu; Zhiguo Liu; Yacheng Wang; Jiaming Cai; Lingjie Peng (Environmental Science and Pollution Research, 2019)

The Association Between Myocardial Fibrosis and Depressed Capillary Density in Rat Model of Left Ventricular Hypertrophy - Ying Xiao; Yinjie Liu; Jiaming Liu; Y. James Kang (Cardiovascular Toxicology, 2018)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)

Chemical and isotopic constrains on the origin of brine and saline groundwater in Hetao plain, Inner Mongolia - Jun Liu; Zongyu Chen; Lijuan Wang; Yilong Zhang; Zhenghong Li; Jiaming Xu; Yurong Peng (Environmental Science and Pollution Research, 2016)

Genetic mapping and molecular marker development for Pi65(t), a novel broad-spectrum resistance gene to rice blast using next-generation sequencing - Wenjing Zheng; Yan Wang; Lili Wang; Zuobin Ma; Jiaming Zhao; Ping Wang; Lixia Zhang; Zhiheng Liu; Xiaochun Lu (Theoretical and Applied Genetics, 2016)

A spatial-temporal analysis of urban recreational business districts: A case study in Beijing, China - He Zhu; Jiaming Liu; Chen Chen; Jing Lin; Hui Tao (Journal of Geographical Sciences, 2015)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)

A Highly Sensitive Solid Substrate Room Temperature Phosphorimetry for Carbaryl Detection Based on its Activating Effect on NaIO4 Oxidizing Fluorescein - Jiaming Liu; Qitong Huang; Zhen-bo Liu; Xiaofeng Lin; Li-Hong Zhang; Chang-Qing Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2014)

Highly Sensitive Fluorescent Probe for Clenbuterol Hydrochloride Detection Based on its Catalytic Oxidation of Eosine Y by NaIO4 - Jiaming Liu; Zhen-bo Liu; Qitong Huang; Chang-Qing Lin; Xiaofeng Lin (Journal of Fluorescence, 2014)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)

The Arg194Trp polymorphism in the XRCC1 gene and cancer risk in Chinese Mainland population: a meta-analysis - Jin Huang; Jie Zhang; Yuliang Zhao; Banghua Liao; Jiaming Liu; Ling Li; Mingheng Liao; Lanlan Wang (Molecular Biology Reports, 2011)

Attractive model and marketing implications of Theme Shopping Tourism destination - Jiaming Liu; Run Wang (Chinese Geographical Science, 2010)

Factors of spatial distribution of recreation areas in peri-urban Beijing - Jiaming Liu; Run Wang; Tian Chen (Journal of Geographical Sciences, 2010)